ByzRev 03.2021.036: Robert H. Jordan – Rosemary Morris (Hrsg.), The Life and Death of Theodore of Stoudios: (Dumbarton Oaks Medieval Library 70). Cambridge, MA – London: Harvard University Press 2021. - Pratsch, Thomas (The Byzantine Review, 2021)
Robert H. Jordan – Rosemary Morris (Hrsg.), The Life and Death of Theodore of Stoudios (Dumbarton Oaks Medieval Library 70). Cambridge, MA – London: Harvard University Press 2021. 382 S. – ISBN 978-0-6742-6119-8 (31.50 €)